Continuous linear representations - Magyar, Zoltan (North-Holland mathematics studies, 1992)
This monograph gives access to the theory of continuous linear representations of general real Lie groups to readers who are already familiar with the rudiments of functional analysis and Lie groups. The first half of the book is centered around the relation between a continuous linear representation (of a Lie group over a Banach space or even a more general space) and its tangent; the latter is a Lie algebra representation in a sense. Starting with the Hille-Yosida theory, quite recent results are reached. The second half is more standard unitary theory with applications concerning the Galilean and Poincar groups. Appendices help readers with diverse backgrounds to find the precise descriptions of the concepts needed from earlier literature. Each chapter includes exercises.